Helicopter Services in India: Evidence from Northeastern States. (December 2022) - Tripathi, S.N.; Alok, V.N.; Panda, Pradeep Kumar
The helicopter service in Northeast (NE) India was introduced in 1992–1993 to provide connectivity to passengers in remote areas of the region and with other states and union territories of India at affordable cost. It also intended to evacuate people during natural calamities and medical emergencies. By the year 2021, the helicopter services were operational in seven NE states, namely, Arunachal Pradesh (1995), Sikkim (1998), Meghalaya (1999), Tripura (2002), Nagaland (2007), Mizoram (2012) and Manipur (2018). The article intends to examine the efficiency and usefulness of the helicopter scheme in the North Eastern Region, to find out the extent to which the scheme has facilitated connectivity for different layers of end-users and to identify the key bottlenecks and challenges faced during the implementation of the scheme. With positivist frame of evaluation, both quantitative and qualitative research methods have been used for data collection and analysis. The study was conducted in seven states, and a total of 384 respondents was sampled. During the period 2016–2017, 2017–2018 and 2018–2019, the budget sanctioned by the Ministry of Home Affairs for the scheme was ₹86 crore, ₹86 crore and ₹90 crore, respectively, which had been fully utilised by the state governments. During 2019–2020, ₹100 crore was sanctioned, and the entire amount was utilised. The budget amount was reduced to ₹42 crore in the year 2020–2021. From 2016–2017 to 2019–2020, the overall efficiency in Northeastern Region was a positive trend; although, it declined in 2018–2019 due to a significant decline in the number of passengers in Nagaland and Sikkim despite a marginal decline in the input variable, that is, number of flying hours. Among the sampled beneficiaries, women's participation was 22%, SCs represented 24%, and STs and OBCs represented 31% and 12%, respectively. This shows that the scheme is inclusive. In addition, the flying hours were optimally utilised, and scheme catered to the designated objectives.